2019
DOI: 10.3892/mmr.2019.10317
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑217 inhibition relieves cerebral ischemia/reperfusion injury by targeting SIRT1

Abstract: Micrornas (mirs) have been proposed to be involved in the pathological processes of cerebral ischemia/reperfusion (cir) injury. The present study aimed to investigate the potential role and molecular mechanisms of mir-217 in the regulation of neuronal survival in cir injury. To perform the investigation, an in vitro cellular model of cir injury was established by treating neurons with oxygen-glucose deprivation and reoxygenation (oGd/r). mir-217 levels in neurons were detected using reverse transcription-quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…They are involved in various cellular physiological processes, such as energy metabolism, oxidative stress, and apoptosis. Their ability to resist oxidative stress has been widely studied in cerebral ischemia-reperfusion (Hou et al, 2010;Rothgiesser et al, 2010;Morris et al, 2011;She et al, 2018;Wang et al, 2018;Wu D. et al, 2018;Chang et al, 2019;Duan et al, 2019;Fusco et al, 2019;Rao et al, 2019;Xian et al, 2019;Zhao B. et al, 2019). SIRT1 activates the FOXO family, and FOXO3a has the ability to resist anti-oxidative stress and enhances ROS scavenging activity (Hou et al, 2010).…”
Section: Sirt/foxo Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…They are involved in various cellular physiological processes, such as energy metabolism, oxidative stress, and apoptosis. Their ability to resist oxidative stress has been widely studied in cerebral ischemia-reperfusion (Hou et al, 2010;Rothgiesser et al, 2010;Morris et al, 2011;She et al, 2018;Wang et al, 2018;Wu D. et al, 2018;Chang et al, 2019;Duan et al, 2019;Fusco et al, 2019;Rao et al, 2019;Xian et al, 2019;Zhao B. et al, 2019). SIRT1 activates the FOXO family, and FOXO3a has the ability to resist anti-oxidative stress and enhances ROS scavenging activity (Hou et al, 2010).…”
Section: Sirt/foxo Signaling Pathwaymentioning
confidence: 99%
“…SIRT1 also activates the peroxisome proliferator-activated receptor γ coactivator-1PGC1α (a transcriptional coactivator of oxidative stress) and exerts an antioxidant effect (Morris et al, 2011). By targeting SIRT1 or regulating the SIRT1 related pathway, neurons will be protected from CIRI-induced mitochondrial oxidative stress and inflammatory response (Duan et al, 2019;Fusco et al, 2019;Rao et al, 2019;Xian et al, 2019). Inflammatory cytokines can enhance the activity of SIRT2 in cells, enhance its deacetylation of NF-κB, reduce the transcriptional activity of NF-κB, and reduce the expression of inflammatory mediators, such as interleukin-6 (IL-6), matrix metalloproteinase 9 (MMP9), and cyclooxygenase-2 (COX-2), to exert antioxidant and anti-inflammatory effects (Rothgiesser et al, 2010).…”
Section: Sirt/foxo Signaling Pathwaymentioning
confidence: 99%
“…Although glucose and oxygen deprivation can be attenuated by reperfusion of cerebral blood, the process of reperfusion exacerbates the inflammatory response, oxidative stress and apoptosis, which further aggravates the progression of cerebral damage caused by reperfusion (31)(32)(33). Previous studies have demonstrated that the inhibition of the inflammatory response, oxidative stress and apoptosis rescued cells from OGD/R injury (34,35). Gaire et al (36) reported that Terminalia chebula extract prevented OGD/R injury in PC12 cells and suppressed lipopolysaccharide-induced activation of microglia through inhibition of the oxidative and inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Yin et al (Yin et al 2010) rst reported that miR-497 aggravated ischemic neuronal death by directly binding to the predicted 3'UTR target sites of Bcl-2/Bcl-w genes. Similarly, downregulation of miR-217 signi cantly ameliorated oxygen-glucose deprivation and reoxygenation (OGD/R)-induced neuron injury, in ammatory responses and oxidative stress by targeting sirtuin 1 (SIRT1) (Rao et al 2019). Inversely, miR-132 could attenuate cerebral injury by protecting blood-brain barrier disruption in ischemia stroke (Zuo et al 2019).…”
Section: Introductionmentioning
confidence: 99%